2007
DOI: 10.1037/0893-3200.21.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and physical health symptoms among women seeking help for relationship aggression.

Abstract: This study examined associations between intimate partner aggression and physical health symptoms among a sample of help-seeking women experiencing relationship aggression (N = 388). Using a structural equation modeling framework, the authors found posttraumatic stress disorder (PTSD) symptoms to fully mediate the associations of both physical and psychological aggression with physical health symptoms. The influence of PTSD symptoms on physical health symptoms was partially mediated by anger/irritability. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 52 publications
4
39
2
Order By: Relevance
“…Severity of IPV was associated with resilience, and women who experienced more severe IPV in the past 12 months were less likely to be resilient. This is consistent with research that shows a strong dose-response relationship between severity of abuse and mental ill health [27,4247]. Other research has shown that due to social isolation by perpetrators, women who experience severe IPV are less likely to disclose abuse and receive social support from their informal networks or from formal services [48].…”
Section: Discussionsupporting
confidence: 87%
“…Severity of IPV was associated with resilience, and women who experienced more severe IPV in the past 12 months were less likely to be resilient. This is consistent with research that shows a strong dose-response relationship between severity of abuse and mental ill health [27,4247]. Other research has shown that due to social isolation by perpetrators, women who experience severe IPV are less likely to disclose abuse and receive social support from their informal networks or from formal services [48].…”
Section: Discussionsupporting
confidence: 87%
“…A few studies have noted a positive relationship between psychological abuse and women's symptoms after controlling for physical abuse (Mechanic, Weaver, & Resick, 2008;Taft, Vogt, Mechanic, & Resick, 2007). However, our findings are not consistent with previous reports that demonstrated a positive association between IPV severity and chronic pain (Coker et al, 2005;Wuest et al, 2008).…”
Section: Discussioncontrasting
confidence: 67%
“…The current study suggests that individuals and couples do in fact benefit from reducing aggression, as would be expected based on the links between partner aggression and relationship and individual functioning (e.g., Lawrence and Bradbury 2007;Taft et al 2007). Reductions in physical aggression did not predict greater relationship satisfaction, but did predict greater relationship investment and commitment across treatment conditions, hinting that couples may be more hopeful and more likely to devote resources to their relationships when physical aggression is less frequent.…”
Section: Discussionmentioning
confidence: 79%